Reversing Size‐Dependent Trends in the Oxidation of Copper Clusters through Support Effects. Issue 1 (22nd December 2017) - Mammen, Nisha; Spanu, Leonardo; Tyo, Eric C.; Yang, Bing; Halder, Avik; Seifert, Sönke; Pellin, Michael J.; Vajda, Stefan; Narasimhan, Shobhana
Abstract : Having the ability to tune the oxidation state of Cu nanoparticles is essential for their utility as catalysts. The degree of oxidation that maximizes product yield and selectivity is known to vary, depending on the particular reaction. Using first principles calculations and XANES measurements, we show that for subnanometer sizes in the gas phase, smaller Cu clusters are more resistant to oxidation. However, this trend is reversed upon deposition on an alumina support. We are able to explain this result in terms of strong cluster‐support interactions, which differ significantly for the oxidized and elemental clusters. The stable cluster phases also feature novel oxygen stoichiometries. Our results suggest that one can tune the degree of oxidation of Cu catalysts by optimizing not just their size, but also the support they are deposited on. Abstract : We show that small Cu clusters supported on alumina are more easily oxidized than clusters of larger size, reversing the trend seen in the gas phase. This is traced to the crucial role of cluster‐support interactions in determining oxidizability. Our work suggests the oxidation state, and thus catalytic performance, of Cu clusters can be tuned by optimizing not just size but also the support.